1992
DOI: 10.1007/bf00198984
|View full text |Cite
|
Sign up to set email alerts
|

Sublinear summation of responses in locust photoreceptors

Abstract: Summary. The response of a locust, Locusta miyratoria,photoreceptor to a simultaneous pair of dim flashes is smaller than the sum of the responses to the individual component flashes, even when the photon absorption sites are separated by a distance of 120 ~tm, which should prevent them from interacting biochemically. A similar depression is observed when a flash is paired with a depolarizing current instead of a second flash, irrespective of whether the flash response precedes or follows the current response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In these terms, the behavior of a light-adapted photoreceptor is much simpler than a dark-adapted one, and the NLN model (with only second-order nonlinearity) fitted the responses quite well with a small residual mean square error. The output nonlinearity seems to be a simple compression, consistent with self-shunting of the membrane (Laughlin, 1981) enhanced by voltage-dependent mechanisms (Pece and French, 1992). Increased activation or deactivation of sion of the membrane potential range in light-adapted blowfly photoreceptors (Weckstrom et al, 1991).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In these terms, the behavior of a light-adapted photoreceptor is much simpler than a dark-adapted one, and the NLN model (with only second-order nonlinearity) fitted the responses quite well with a small residual mean square error. The output nonlinearity seems to be a simple compression, consistent with self-shunting of the membrane (Laughlin, 1981) enhanced by voltage-dependent mechanisms (Pece and French, 1992). Increased activation or deactivation of sion of the membrane potential range in light-adapted blowfly photoreceptors (Weckstrom et al, 1991).…”
Section: Discussionmentioning
confidence: 83%
“…Although the Hammerstein model gave a better fit to the data than a second-order Volterra system, there is significant evidence available for nonlinearities at the end of the phototransduction process. These include self-shunting of the light-induced conductance and voltage-activated conductances (Laughlin, 1981;Laughlin and Weckstrom, 1989;Weckstrom et al, 1991;Pece and French, 1992;Tsukahara, 1980). We therefore added a second static nonlinear component to the Hammerstein model to produce the nonlinear/ linear/nonlinear sandwich model (NLN model) shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although linear convolution with a filter function provided a close description to single flash responses and random fluctuations around a mean light intensity, insect photoreceptors clearly demonstrate nonlinear adaptation, even under asymptotically small signal conditions (Marmarelis and McCann, 1977; Laughlin and Hardie, 1978; Pece and French, 1992). Nonlinear analyses of flash responses and frequency responses suggested that the processes between light absorption and membrane conductance change included both an early gain reduction and a late saturation with light intensity (Weckström et al, 1988; Pece et al, 1990; French et al, 1993).…”
Section: Introductionmentioning
confidence: 99%